2015
DOI: 10.3109/01902148.2015.1090501
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 modulates human airway smooth muscle cell proliferation and migration in asthma through regulation of PTEN expression

Abstract: This study provides the first in vitro evidence that overexpression of miR-21 in HASM cells can trigger cell proliferation and migration, and the effects of miR-21 depend on the level of PTEN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…Both C3 and C4 showed eleven genes with identical dysregulation and similar fold change magnitude (Supplemental Table E9). Supplemental Figure E2 illustrates the expression of 5 genes common to both clusters that have been previously linked to airway biology and asthma: TNFAIP3 (1820); MIR21 (21, 22); HLA-DQA1 (23, 24); IL1RAP (25); and CCL18 (2628). …”
Section: Resultsmentioning
confidence: 99%
“…Both C3 and C4 showed eleven genes with identical dysregulation and similar fold change magnitude (Supplemental Table E9). Supplemental Figure E2 illustrates the expression of 5 genes common to both clusters that have been previously linked to airway biology and asthma: TNFAIP3 (1820); MIR21 (21, 22); HLA-DQA1 (23, 24); IL1RAP (25); and CCL18 (2628). …”
Section: Resultsmentioning
confidence: 99%
“…8 The promoting role of miR-21 on human airway SMC proliferation and migration has been previously investigated. 21 Interestingly, miR-21-5p was found to regulate the expression of apoptosis-related factors, inhibiting cellular apoptosis. 22 The inhibition of miR-21-5p reduced proliferation and invasion, but elevated apoptosis of colon adenocarcinoma cells and esophageal squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, microRNA 21 (miR‐21) has been found to be the most highly upregulated miRNA in the lungs of asthmatic mice (T. X. Lu, Munitz, & Rothenberg, ). Further study has indicated that the overexpression of miR‐21 promotes human ASMC proliferation by targeting phosphatase and tensin homolog deleted on chromosome ten (PTEN; Y. Liu et al, ). However, the specific mechanisms underlying the upregulation of miR‐21 in ASMCs and the mechanisms by which miR‐21 induces ASMC proliferation are still unclear.…”
Section: Introductionmentioning
confidence: 99%